Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1109/tdei.2003.1194122
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet-based denoising of partial discharge signals buried in excessive noise and interference

Abstract: Achieving acceptable levels of sensitivity during on-line and/or on-site partial discharge (PD) measurements still continues to remain a very challenging task, primarily due to strong coupling of external (random, discrete spectral and stochastic pulsive) interferences. Many analog and digital approaches have been proposed for suppressing these interferences, and amongst these, rejection of the pulsive type of interferences is known to be vvry diffcult, if not impossible. The time and frequency characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
134
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(149 citation statements)
references
References 11 publications
0
134
0
4
Order By: Relevance
“…Thus, to be recognized as DP, the detected signal should appear with sufficient recurrence and be large enough to be considered as something other than just random noise.The main sources of noise are divided in four categories classified by the type of interferences produced [25]:…”
Section: Noise Sourcementioning
confidence: 99%
“…Thus, to be recognized as DP, the detected signal should appear with sufficient recurrence and be large enough to be considered as something other than just random noise.The main sources of noise are divided in four categories classified by the type of interferences produced [25]:…”
Section: Noise Sourcementioning
confidence: 99%
“…The signals were acquired in laboratory in a realistic manner [14]. For processing the signals, the mother wavelet was selected after rigorous trials through 'db1' to 'db45' and 'bior 1.1' to 'bior 6.8'.…”
Section: Resultsmentioning
confidence: 99%
“…We started from a set of candidate wavelet families already used by other authors [12,13,15,17] such as Daubechies (db), Symlets (sym), Biorthogonal (bio), Coiflets (coif); in particular, by taking into account wavelets of different orders, the performances of a total number of 60 wavelets were compared.…”
Section: Wavelet Selectionmentioning
confidence: 99%
“…WPT has also been used recently for UWB impulse radio signal denoising [11], although the authors do not comment on possible limitations and drawback of the adopted technique. Satish and Nazneen [12] used the DWT for extracting PD pulses buried in very high levels of noise and interferences and showed that the results obtained with the proposed wavelet-based denoising technique were superior with respect to those obtained with different digital filtering approaches, such as the FIR (Finite Impulse Response) method and the IIR (Infinite Impulse Response)-notch filter method. In the paper they underlined the importance for best results of an optimal choice of the mother wavelet and of the number of levels for decomposition-reconstruction of the input signal, but they did not deal with such a topic.…”
mentioning
confidence: 99%